Preoperative neutrophil-to-lymphocyte ratio as a prognosticator in early stage pancreatic ductal adenocarcinoma. Issue 10 (October 2018) - Abe, Tomoyuki; Amano, Hironobu; Kobayashi, Tsuyoshi; Hanada, Keiji; Nakahara, Masahiro; Ohdan, Hideki; Noriyuki, Toshio
Abstract: Background: The neutrophil-to-lymphocyte ratio (NLR), which reflects the cancer-induced systemic inflammation response, has been proposed as a risk factor for poor long-term prognosis in cancer. We investigated the prognostic role of the NLR and the relationship between the NLR and TNM stage in pancreatic ductal adenocarcinoma (PDAC) patients following curative resection. Methods: One-hundred thirty-eight consecutive patients with resected PDAC were enrolled between 2004 and 2014. Univariate and multivariate analyses identified variables associated with overall survival (OS) and recurrence-free survival (RFS). Patients were stratified according to the NLR, with an NLR cut-off value of 2.2 being estimated by receiver operating characteristic curve. Results: Compared to patients with a low NLR (≤2.2), those with a high preoperative NLR (>2.2) had worse OS and RFS ( P  = 0.017, P  = 0.029, respectively). For early-stage tumors, tumor size ≥20 mm and a high NLR were independent risk factors for poor OS (hazard ratio (HR): 3.255, 95% confidence interval (CI): 1.082–9.789, P  = 0.036; HR: 3.690, 95% CI: 1.026–13.272, P  = 0.046, respectively) and RFS (HR: 3.575, 95% CI: 1.174–10.892, P  = 0.025; HR: 5.380, 95% CI: 1.587–18.234, P  = 0.007, respectively). The NLR was not correlated with prognosis in patients with advanced stages. Conclusions: An elevated preoperative NLR was an important prognosticator for early TNM stage PDAC. The NLR, which is calculated using inexpensive and readily available biomarkers, could be a novel tool for predicting long-term survival in patients, especially those with early stage PDAC.